Faculty Senate, Agenda, November 20, 2008 - Faculty Senate, Valdosta State University (Valdosta, Ga: Valdosta State University Archives and Special Collections, 2008)
Valdosta State University. Faculty Senate, Agenda, November 20, 2008.
1 electronic document. Faculty Senate, Agenda, November 20, 2008. 25 pages.
Keywords: Corporation reports; Valdosta State University. Faculty Senate; Committees; Electronic records